Modular 3D Printed Compressed Air Driven Continuous‐Flow Systems for Chemical Synthesis. Issue 23 (12th June 2019) - Penny, Matthew R.; Rao, Zenobia X.; Peniche, Bruno Felício; Hilton, Stephen T.
Abstract : In this present study, we describe the development of a low‐cost, small‐footprint and modular 3D printed continuous‐flow system that readily attaches to existing stirrer hotplates. Flow‐rates are controlled by compressed air that is typically present in all fume hoods, making it suitable for use by synthetic chemists. The length of the flow‐path and reaction residence time is regulated by control of the air‐flow and pressure and by addition of one or more 3D printed polypropylene (PP) circular disk reactors that were designed to fit a DrySyn Multi‐E base, which is found in most synthetic laboratories. The ease of use of the system, the facile control of flow‐rates and the solvent resistance of the PP reactors was demonstrated in a range of SN Ar reactions to produce substituted ether derivatives highlighting the utility and modularity of the system. Abstract : A low‐cost, small‐footprint, modular 3D printed continuous‐flow system that could be attached to existing stirrer hotplates was developed and tested in a range of SN Ar reactions to produce substituted ether derivatives. Flow‐rates are controlled by compressed air typically present in all fume hoods, and the length of the flow‐path and reaction residence time is regulated by 3D printed polypropylene (PP) circular disk reactors.